2010
DOI: 10.1109/tdsc.2008.53
|View full text |Cite
|
Sign up to set email alerts
|

Steward: Scaling Byzantine Fault-Tolerant Replication to Wide Area Networks

Abstract: Abstract-This paper presents the first hierarchical Byzantine fault-tolerant replication architecture suitable to systems that span multiple wide area sites. The architecture confines the effects of any malicious replica to its local site, reduces message complexity of wide area communication, and allows read-only queries to be performed locally within a site for the price of additional standard hardware. We present proofs that our algorithm provides safety and liveness properties. A prototype implementation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 38 publications
0
87
0
3
Order By: Relevance
“…While "correct" in the traditional sense (both safety and liveness are met), systems vulnerable to such performance degradation are of limited practical use in adversarial environments. We experienced this problem firsthand in 2005, when DARPA conducted a red team experiment on our Steward system [7]. Steward survived all of the tests according to the metrics of safety and liveness, and most attacks did not impact performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While "correct" in the traditional sense (both safety and liveness are met), systems vulnerable to such performance degradation are of limited practical use in adversarial environments. We experienced this problem firsthand in 2005, when DARPA conducted a red team experiment on our Steward system [7]. Steward survived all of the tests according to the metrics of safety and liveness, and most attacks did not impact performance.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that most of the protocols (e.g., [5], [6], [7], [8], [9], [10], [11]) share a common feature: they rely on an elected leader to coordinate the agreement protocol. We call such protocols leader based.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous BFT algorithms have been proposed [19][20][21][22][23][24][25][26][27][28][29]. Many of these algorithms are designed to protect generic stateful servers against Byzantine faulty server replicas and faulty clients.…”
Section: Related Workmentioning
confidence: 99%
“…Steward [22] is a hierarchical replicated state machine architecture for WAN. A group of servers in a site is converted into a logical entity that works as a single participant in a wide-area protocol.…”
Section: Related Workmentioning
confidence: 99%